High resolution non-contact measurement techniques for three-dimensional deformation processes of paperboard laminates. (2017) - Zappa, Emanuele; Liu, Rui; Bolzon, Gabriella; Shahmardani, Mahdieh
Abstract: Full-field non-contact measurement techniques have been widely applied to recover displacement and strain components. These measurements can help understanding the mechanical behavior of materials and verifying the constitutive assumptions. Especially complex material systems benefit from this technique. In this study, we consider the paperboard laminates widely used in beverage packaging, which present different characteristics along different material directions, induced by the relevant manufacture processes. A three-dimensional digital image correlation (3D DIC) technique is applied to understand the mechanical characterization of paperboard laminates by quasi-static inflation experiments. The whole displacement field of the specimens is recovered processing with DIC images from a high resolution stereoscopic camera system. The superior performances of this approach, compared to the formerly exploited laser profilometry methodology, is evidenced.